Beyond coverage: a qualitative study exploring the perceived impact of Gabon's health insurance plan on access to and quality of prenatal care - N'doh Ashken Sanogo; Arone Wondwossen Fantaye; Sanni Yaya (BMC, 2020)
Abstract Background Access to affordable and adequate healthcare in a health system determines the universal health coverage achievement for all residents in a country. Achieving access to healthcare requires the availability of a financing system that ensures access to and provision of adequate care, regardless of the ability to pay. In sub-Saharan Africa, accessibility, use and coverage of prenatal visits are very low and poor, which reduces the quality of care. This paper explored the impact of a social health insurance scheme on the quality of antenatal care in Gabon. Methods This qualitative study involved the analysis of data collected from semi-structured interviews and non-participant observations to assess the quality of antenatal care. The study elicited perceptions on the demand side (pregnant women) and the supply side (health professionals) in health facilities. Fifteen semi-structured interviews were conducted with pregnant women (aged between 15 and 49) and 5 with health professionals, who each had a seniority of at least 10 years, at different levels of care. Nine non-participant observations were also conducted. Coded transcripts were reviewed and analyzed using the Canadian Institute for Public Administration of Citizen-Centered Services model as an analytical guide. Results On the demand side, women were generally satisfied with the prenatal services they receive in health facilities. However, complaints were made about the rudeness of some nurses, the high price of the delivery kit (50,000 XAF), and the fact that some essential medicines for maternity are not covered. On the supply side, participants agreed that compulsory health insurance is important in providing antenatal care access to those who need it the most. However, some problems remain. The participants outlined some logistical problems and a lack of medical equipment, including the stock of drugs, disinfectants, and the absence of clean water. Conclusion Understanding the perceptions of pregnant women and health professionals regarding the quality of antenatal care can help to inform refinements to methods through which the services can be better provided. In addition, the study findings are vital to increasing the use of care, as well as combating high maternal mortality rates. Compulsory health insurance has improved the accessibility and utilization of healthcare services and has contributed to improved quality of care.